Kobiety piszą i rachują - Ewa Kraskowska (Przestrzenie Teorii, 2015)
This article is a review of the multiple-author book titled Księgowanie. Literatura, kobiety, pieniądze [Bookkeeping: Literature, Women, and Money], which was published by Szczecin University Press in 2014. The collection contains articles that are devoted to the economic aspects of Polish women’s lives, as they have been discussed in literature (i.e. fiction, autobiographical and journalistic writings, etc.) from Romanticism until the present day, with particular focus on the financial situation of women writers.